Predicting factors of blood pressure normalization in hypertensive patients after short-term follow-up - Sall, Fatouma; Meneas, Gueu Christophe; Siransy, Balayssac Ahou Edwige; N’cho Mottoh, Marie-Paule; Kpi, Yannik-Hermann; N’guessan, Ismael; Assi, Vierge Marie; Diby, Florent; Adoubi, Anicet (Frontiers in Cardiovascular Medicine, 2024)
Introduction Normalization of blood pressure in hypertensive patients is a major challenge for practitioners. Knowledge of the factors associated with normalization of blood pressure could help optimize management of these hypertensive patients. In this study, we analysed the factors predictive of this in a population of hypertensive patients followed as outpatients in a specialised department. Patients and methods Retrospective and analytic study (January 2021–May 2022) of adult hypertensive patients over 40 years old who had been receiving antihypertensive treatment as outpatients in the Cardiology Department of the Bouake Teaching Hospital for at least 6 months. We studied the epidemiological and clinical parameters as well as the factors involved in the normalization of blood pressure in this population. Statistical analysis was performed using SPPS version 26 software (SPSS Inc., Chicago, IL, USA). Results We collected 194 patients records (57.7% women). The mean age was 59.13 years [extremes: 40–89 years]. One hundred and nine (56.2%) patients had a low socioeconomic status and 151 (77.83%) had at least 2 cardiovascular risk factors. The mean systolic blood pressure on admission was 171.12 ± 22.38 mmHg [extremes: 140–259 mmHg] and the mean diastolic blood pressure was 97.98 ± 17.83 mmHg [extremes: 60–168 mmHg]. First-line treatment consisted of dual anti-hypertensive therapy (n = 133; 68.55%) and fixed combination (n = 152; 78.35%). Only 25.25% (n = 49) of patients achieved normalization of blood pressure with therapeutic adherence estimated at 37.62% (n = 73). In multivariate analysis adjusted for anti-hypertensive treatment adherence, age (OR = 1.03; 95% CI = 1.002–1.059; p = 0.039), absence of alcoholism (OR = 9.48; 95% CI = 2.13–42.11; p = 0.003), number of cardiovascular risk factors <2 (OR = 1.52; 95% CI = 1.06–2.16; p = 0.021), normalization of uricemia (OR = 1.05; 95% CI = 1.00–1.11; p = 0.039) and natraemia (OR = 1.01; 95% CI = 1.00–1.03; p = 0.021), dual therapy (OR = 0.40; 95% CI = 0.18–0.90; p = 0.027), change in treatment for optimization (OR = 4.22; 95% CI = 1.71–10.37; p = 0.002), intellectual education (OR = 10.40; 95% CI = 4.31–25.10; p < 0.001) and health insurance (OR = 0.09; 95% CI = 0.04–0.21; p < 0.001) were the main factors predicting normalization of blood pressure. Conclusion Control of cardiovascular risk factors and compliance with treatment are the main factors in normalizing blood pressure.